2023
DOI: 10.1007/s11301-023-00327-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review on technological transformation in SMEs: a transformation encompassing technology assimilation and business model innovation

Abstract: Small and medium-sized enterprises (SMEs) are pushed to introduce new technologies due to different requirements and changes in the business setting. The SMEs' transformation to exploit new technologies is challenging given their lack of resources and the complexity of technological transformation, which encompasses technology assimilation and business model innovation (BMI). Although studies recognize the complementarity of technology assimilation and BMI for benefiting from technology, the literature is frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…The benefits of digitalization have been extensively studied, and prior research has indicated that SMEs can leverage digital technologies to improve their value-creation activities, thereby enhancing their digitalization efforts (Broccardo et al , 2023; Sengupta et al , 2021; Warner and Wäger, 2019). BMI has emerged as a critical dimension of how firms create value based on available resources and capabilities in intra- or inter-organizational processes ( de Mattos et al ., 2023; Clauss, 2017). Thanks to digitalization, SMEs have benefited from a more integrated perspective of BMI (Xie et al , 2022).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…The benefits of digitalization have been extensively studied, and prior research has indicated that SMEs can leverage digital technologies to improve their value-creation activities, thereby enhancing their digitalization efforts (Broccardo et al , 2023; Sengupta et al , 2021; Warner and Wäger, 2019). BMI has emerged as a critical dimension of how firms create value based on available resources and capabilities in intra- or inter-organizational processes ( de Mattos et al ., 2023; Clauss, 2017). Thanks to digitalization, SMEs have benefited from a more integrated perspective of BMI (Xie et al , 2022).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…This governance framework is critical because it provides a disciplined way to incorporate cybersecurity into all parts of digital operations, ensuring that security considerations are entrenched throughout the technology adoption and deployment process. The literature also emphasizes the importance of incorporating risk management into digital planning, such as completing comprehensive risk assessments and strategic planning to manage and mitigate security threats [48]. Risk management procedures are critical for recognizing potential vulnerabilities and taking proactive steps to remedy them before they are exploited.…”
Section: Findings Strategic Integration Of Digital Transformation And...mentioning
confidence: 99%
“…Such an institute would serve as a centralized entity, providing SMEs with resources, training, and assistance to improve their cybersecurity infrastructure. Offering specialist advice and facilitating access to cutting-edge technologies could help SMEs adopt best practices and implement effective security processes, thereby reducing the risks associated with cyber threats [48]. This policy would ensure that SMEs, which often need more knowledge and resources to develop comprehensive cybersecurity policies independently, receive the support they need to protect their digital assets effectively.…”
Section: Critique Of the Extant Literature To Identify The Future Of ...mentioning
confidence: 99%
“…Since the research focuses on development and the state of the art of risk management in SMEs under the digital transformation, the author presents the research gap by exploring literature related to digital transformation, SMEs and risk management (as depicted in Figure 1). Digital transformation can be viewed as an organizational transformation process for SMEs due to investing or adopting advanced technology [22]. For instance, SMEs would adopt digital technology in functional activities such as engineering, marketing and supply chain, developing digital service or products, using apps, platform to connect with customers, and redesigning business model based on advanced technology.…”
Section: Step One: Identification Of the Research Topic And Gapmentioning
confidence: 99%